NHL Entry into the Chinese Market - Liška, Ladislav (2020)
This thesis deals with the entry of the American professional hockey league NHL into the Chinese market. The main objective of the thesis is to examine the state of the Chinese sports market and determine the chances of the NHL to successfully enter the market. Besides that, the main objective of the work presupposes proposing appropriate suggestions to increase the probability of successful market penetration. The first part of the main objective of the thesis is achieved through the detailed elaboration of the state sports policy, monitoring the situation on the Chinese sports market, including a description of NHL’s competition and trends and identification of a typical Chinese sports consumer. The second part of the main objective is achieved by using SWOT analysis of marketing activities of NHL in China and their comparison with the knowledge gained in the theoretical part of the thesis. Also, using data obtained from qualitative research, conducted through in-depth semi-structured interviews with representatives of the NHL target group in China to bring new notions and ideas. This thesis provides a detailed overview of the current situation in the Chinese sports market, current trends affecting the Chinese consumer and recommendations for NHL are also applicable to other similarly focused entities.